The Role of the Interplay Between Autophagy and NLRP3 Inflammasome in Metabolic Disorders - Lv, Shuangyu; Wang, Honggang; Li, Xiaotian (Frontiers in Cell and Developmental Biology, 2021)
Autophagy is an important and conserved cellular pathway in which cells transmit cytoplasmic contents to lysosomes for degradation. It plays an important role in maintaining the balance of cell composition synthesis, decomposition and reuse. Autophagy participates in a variety of physiological and pathological processes. The nucleotide-binding oligomerization domain-like receptor family, pyrin domain-containing 3 (NLRP3) inflammasome is a macromolecular complex that can activate caspase-1 to induce the maturation and secretion of Interleukin-1beta (IL-1β) and IL-18. NLRP3 inflammasome is related with many diseases. In recent years, it has been reported that the interplay between autophagy and NLRP3 inflammasome plays an important role in many diseases. In this review, we summarized the recent studies on the interplay between autophagy and NLRP3 inflammasome in metabolic disorders to provide ideas for the relevant basic research in the future.